Clinically practical pharmacometrics computer model to evaluate and personalize pharmacotherapy in pediatric rare diseases: application to Graves' disease - Steffens, Britta; Koch, Gilbert; Gächter, Pascal; Claude, Fabien; Gotta, Verena; Bachmann, Freya; Schropp, Johannes; Janner, Marco; l'Allemand, Dagmar; Konrad, Daniel; Welzel, Tatjana; Szinnai, Gabor; et al. (Frontiers in Medicine, 2023)
Graves’ disease (GD) with onset in childhood or adolescence is a rare disease (ORPHA:525731). Current pharmacotherapy approaches use antithyroid drugs such as carbimazole in monotherapy or in combination with thyroxine hormone substitutes such as levothyroxine as block-and-replace therapy in order to normalize thyroid function and improve patients’ quality of life. However, in the context of fluctuating disease activity, especially during puberty, a considerable portion of pediatric patients with GD is suffering from thyroid hormone concentrations outside the therapeutic reference ranges. Our main goal was to develop a clinically practical pharmacometrics computer model that characterizes and predicts individual disease activity in children with various severity of GD under pharmacotherapy. Disease severity was defined based on free thyroxine (FT4) at diagnosis according to current guidelines. A retrospective multi-center study was conducted to collect data in children with mild, moderate, or severe GD. Data from 44 children with GD (75% female, median age 11 years, 62% receiving monotherapy) were analyzed. FT4 measurements were collected in 13, 15, and 16 pediatric patients with mild, moderate, or severe GD with median FT4 at diagnosis of 59.9 pmol/l [IQR 48.4, 76.8], and a total of 494 FT4 measurements during a median follow-up of 1.9 years [IQR 1.69, 1.97]. We observed no notable difference between severity groups in terms of patient characteristics, daily carbimazole starting doses as well as patient years. The final pharmacometrics computer model was developed based on FT4 measurements and on carbimazole or on carbimazole and levothyroxine doses involving two clinically relevant covariate effects, age at diagnosis and disease severity. In conclusion, we present a tailored pharmacometrics computer model that is able to describe individual FT4 dynamics under both, carbimazole monotherapy and carbimazole/levothyroxine block-and-replace therapy accounting for inter-individual disease progression and treatment response in children and adolescents with GD. Such clinically practical and predictive computer model has the potential to facilitate and enhance personalized pharmacotherapy in pediatric GD, reducing over- and underdosing and avoiding negative short- and long-term consequences. Prospective randomized validation trials are warranted to further validate and fine-tune computer-supported personalized dosing in pediatric GD and other pediatric rare diseases.